A Multidisciplinary Frame for Studying Democratic Shifts in Southeast Asia : Mixing Politics, Sociology And Psychology Across Historical Time - Montiel, Cristina Jayme (Archīum Ateneo, 2015)
outheast Asia has been a showcase for democratic transitions in the past 30 years. This paper proposes a conceptual lens for studying political shifts in the Southeast Asian region. The argumentative storyline follows two fundamental propositions about democratic transitions. My first proposition is that during democratic transitions, human phenomena arise on nested analytical layers namely the global arena, the state, prodemocracy movements, and individuals. Each layer is conventionally studied by international relations, political science, sociology, and psychology respectively. I propose a multidisciplinary lens that transverses all these analytical layers. A second proposition is that during political shifts, social conditions are historically-situated. Historicity is anchored on stages of democratization, namely the authoritarian regime, toppling the regime, power shift, state building, and nation building. This paper describes a 4 x 5 matrix (analytical layer x historical stage) that may guide a regional agenda on the empirical study of democratic transitions in the Southeast Asian region. It likewise gives examples of research findings in Philippine-based studies that have already begun to provide empirical data about segments of this research matrix.